eval_UASI PENGGUNAAN ANTIBIOTIK DENGAN METODE GYSSENS PADA PASIEN PNEUMONIA DI BALAI BESAR KESEHATAN PARU MASYARAKAT (BBKPM) MAKASSAR - Arifin, Erlin Putri Hendrawati (Fakultas Farmasi Institut Kesehatan DELI HUSADA Deli Tua, 2025)
Pneumonia is one of the leading causes of death in children under five, particularly in developing countries such as Indonesia. Antibiotics are the mainstay of therapy for bacterial pneumonia; however, inappropriate use can lead to resistance and treatment failure. This study aims to eval_uate the rationality of antibiotic use in pediatric pneumonia patients at the Public Lung Health Center (BBKPM) Makassar using the Gyssens method. This was a descriptive study conducted from April to June 2025 using retrospective medical record data from 33 pediatric inpatients aged 1–5 years diagnosed with pneumonia and receiving antibiotic therapy from January to December 2024. Antibiotic rationality was assessed using the Gyssens algorithm, which classifies antibiotic use into category 0 (rational) and categories I–VI (irrational). The results showed that out of 64 antibiotic prescriptions, 20 (31%) were categorized as rational (category 0), while 44 (69%) were irrational. The highest proportion of irrational use was category III B (34%) for too-short duration, followed by category IV A (31%) for suboptimal effectiveness, and IV B (3%) for safety concerns. No cases were found in categories I, II, III A, IV C, IV D, V, or VI. These findings indicate that while some antibiotic use was appropriate, a significant portion was not, highlighting the need for regular eval_uation and better adherence to clinical guidelines to optimize antibiotic therapy and reduce resistance risks in pediatric pneumonia treatment.